Investigation of the effect of MDM2 SNP309 and TP53 Arg72Pro polymorphisms on the age of onset of cutaneous melanoma - Cotignola, Javier Hernan (2012)
Melanoma accounts for the majority of deaths from skin cancer. Women tend to be diagnosed at a younger age and have better survival than men. A tumor-host interaction might be responsible for these gender-specific differences. Recently, a functional single-nucleotide polymorphism in the promoter of the human homolog of mouse double minute 2 (MDM2) gene was characterized: single-nucleotide polymorphism (SNP)309 increases the MDM2 transcription. In melanoma, the effects for SNP309 and the related tumor protein p53 (TP53) Arg72Pro are inconsistent among published reports. This study investigated the association between SNP309 (RefSNP accession ID (rs)2279744) and TP53 codon 72 (rs1042522) polymorphisms, with outcome in a hospital-based cohort of 990 patients with melanoma. We assessed whether these polymorphisms were associated with clinicopathological and phenotypic characteristics and whether these SNPs affect the age of onset of the disease, recurrence, and survival. No significant associations were found between the SNPs and survival. However, women carrying the SNP309 GG genotype were less likely to be diagnosed at a younger age: odds ratioadjusted<50 0.52 (0.29-0.92). Our results suggest that women carrying the SNP309 GG genotype might be at lower risk of developing melanoma at a younger age compared with those carrying TG or TT. Further studies are needed to determine whether a nearby functional polymorphism is responsible for this effect in premenopausal women.